Do grupo de fãs: considerações psicanalíticas - Ranier, Marcela Mello (2009)
The proposal of this dissertation is to understand the psychic aspects that are concerned in the dynamics of a fan club mediated by an idolatry object, taking as reference the Freudian psychoanalytic study. The love on the part of the fan can seem something inexplicable to the first view, however it is of deep importance for who tries it, so much that this fan opts to concentrate in groups returned for the cult of his/her love object, maintaining an identity common with the other participants. In the case the one that refers our research subject, what happens with the fan, it is that when joining the other ones equal that share the feeling of common admiration, is not observed of any promise or possibility of improvement of his/her life or of his/her enlargement. That subject is one of the central of our research, and, for that reason, we will treat of the own process of construction of the groups of fans and in the way of existent relationship among the participant members of the same ones, starting from the analysis of the speech of fans belonging to fan clubs. Therefore, the understanding of that feeling of the fan, so much in the literal sense as in the one of the psychic universe, it evidences, on one side, an imaginary bow that he/she has a private function for the mimicry and, for other, a condition of admiration that makes possible a recognition of the other simbolic. Another parameter of analysis of the fan clubs is the artificial groups analyzed by Freud (1921/1996), where it was verified that the fan club can be identified as a type mass that introduces as much differences as similarities in relation to these groups.